2021
DOI: 10.1108/ijppm-12-2020-0633
|View full text |Cite
|
Sign up to set email alerts
|

Industry 4.0 and green supply chain practices: an empirical study

Abstract: PurposeThe purpose of this study is to examine the impact of Industry 4.0 on economic and environmental performance through the mediation of green supply chain management (GSCM) practices in the emerging economic context, like Pakistan.Design/methodology/approachThis cross-sectional study investigates Industry 4.0 effects on economic and environmental performance through GSCM practices in an emerging economy. For the testing of hypotheses, Smart-PLS is employed. In total, 284 valid responses were analyzed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 85 publications
2
25
0
Order By: Relevance
“…Regarding the effect of GPP on ENTP, the present study demonstrated a positive link between GPP and ENTP ( β = .316, p < .05). The result of this is consistent with the research work of Zhu et al (2013), Umar, Khan, Yusliza, et al (2021), and Ivanova et al (2020). Al‐Ghwayeen and Abdallah (2018) examined the effect of GPP on ENTP.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the effect of GPP on ENTP, the present study demonstrated a positive link between GPP and ENTP ( β = .316, p < .05). The result of this is consistent with the research work of Zhu et al (2013), Umar, Khan, Yusliza, et al (2021), and Ivanova et al (2020). Al‐Ghwayeen and Abdallah (2018) examined the effect of GPP on ENTP.…”
Section: Resultssupporting
confidence: 93%
“…Regarding the effect of GnP in SC, the researchers have demonstrated that GnP/lean practices aid enterprises to mitigate adverse pollutants, waste material, conserve natural resources (Sinha & Anand, 2017; Umar, Khan, Yusliza, et al, 2021), and enhance profitability of firms (Çankaya & Sezen, 2019). Zaid et al (2018) examined the link between GSCM practices and firm performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mughal [75] explored the strong moderating effect of traceability on the connection between eco-design and organizational performance and the association between internal environment management and organizational performance. Umar, Khan [45] further investigated the mediating role of GSCM practices on the relationship of Industry 4.0 to environmental and economic performance.…”
Section: The Mediating Role Of Technological Innovationmentioning
confidence: 99%
“…The use of industry 4.0 is recognized as a vital enabler of circular economy in businesses (Ranta et al, 2021). For example, industry 4.0 enable tracking and sharing of information regarding product and material within the SC process (Khan, Yu, et al, 2021); along with that, it also automates the SC through the use of smart sensors, intelligent machines, and devices which increased the efficiency and quality of resources (Umar et al, 2021), making the system flexible and efficient by increasing the capability of the SC regarding information sharing, coordination, response, and integration hence in turn managing the whole SC process, that is, from production to logistics operation. However, the contemporary research work on the adoption of industry 4.0 technologies lack empirical findings in CE business model (Centobelli et al, 2020) and SC capability, while understanding how industry 4.0 in firms influence CE and SC capability is pivotal.…”
Section: Introductionmentioning
confidence: 99%